2012
DOI: 10.1186/1471-2458-12-766
|View full text |Cite
|
Sign up to set email alerts
|

Number of siblings, birth order, and childhood overweight: a population-based cross-sectional study in Japan

Abstract: BackgroundAlthough several studies have investigated the relationship between the number of siblings or birth order and childhood overweight, the results are inconsistent. In addition, little is known about the impact of having older or younger siblings on overweight among elementary schoolchildren. The present population-based study investigated the relationship of the number of siblings and birth order with childhood overweight and evaluated the impact of having younger or older siblings on childhood overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
76
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 37 publications
17
76
0
2
Order By: Relevance
“…A larger number of siblings decreased the incidence of overweight (P-value<0.001) [25]. Another study done in Los Angeles found children with siblings had lower BMI and were less likely to be obese than children without siblings [26]. A study involving 273 children found the prevalence of an overweight or obese child was 42.5%.…”
Section: Monthly Incomementioning
confidence: 99%
“…A larger number of siblings decreased the incidence of overweight (P-value<0.001) [25]. Another study done in Los Angeles found children with siblings had lower BMI and were less likely to be obese than children without siblings [26]. A study involving 273 children found the prevalence of an overweight or obese child was 42.5%.…”
Section: Monthly Incomementioning
confidence: 99%
“…Previous research has mainly focused on sibship and disease, and has shown that sibship size has a protective effect against allergies 8 and being overweight. 9,10 Epidemiological studies on the relationship between siblings and mental health have mostly come from Western countries, and few studies exist in Asia. A systematic review showed that sibling conflict was significantly associated with more internalizing and externalizing problems among Caucasian subjects, 3 and the most common type of childhood victimization is peer or sibling assault across cultures.…”
mentioning
confidence: 99%
“…Our findings are consistent with previous reports from cross-sectional studies that having younger siblings is associated with a lower risk of being overweight and obesity. [3][4][5][6][7][8] To our knowledge, this study is the first to document a longitudinal association between the birth of a sibling and a lesser subsequent increase in BMIz. Although 1 study reported positive child behavior (eg, greater expression of affection and joyful behavior and less aggression) with a birth interval of >2 years between the child and his/her sibling, 13 no previous study has reported a differential effect of the birth of a sibling on child BMIz based on the child's age when his/her sibling was born.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, there is limited understanding of how the birth of a sibling may relate to changes in BMI longitudinally during early childhood. Monitoring changes in child BMI after the birth of a sibling could help further establish the association between having younger siblings and lower child BMI by examining temporality of events.…”
mentioning
confidence: 99%